Calcific Aortic Stenosis - Inflammatory Disease - Šteiner, Ivo (Ceskoslovenska patologie, 2024)
In developed countries, calcific aortic stenosis (CAS) has become the most common acquired valvular disease and cause for valve replacement. The prevalence of the disease increases with age, reaching over 5 % in adults over 75 years of age. The cases of CAS are classified as either of a previously normal (tricuspid) aortic valve (senile, syn. age - related, "sclerotic" type), or based on a congenitally malformed, usually bicuspid aortic valve. This paper is a brief summary of our 5 previous publications from the years 2007 - 2021, devoted to histopathology of CAS, namely to vascularization, inflammatory infiltrate and metaplastic ossification of the valve, and also to topography of these lesions in individual valve cusps. We conclude that calcification of the aortic valve is not a passive degenerative lesion, but an active multifactorial inflammatory process driven by cells native to the aortic valve. Pathogenesis of CAS is similar to that of atherosclerosis.
Keywords: Pathogenesis; Inflammation; inflammation; Aortic Valve; Aortic Valve Stenosis; Calcinosis; lidé; zánět; calcific aortic stenosis; pathogenesis; probiotics; Aortic valve; aortální chlopeň; aortic valve; aortální stenóza; kalcinóza; Humans